A Highly Water‐Dispersible/Magnetically Separable Palladium Catalyst: Selective Transfer Hydrogenation or Direct Reductive N‐Formylation of Nitroarenes in Water. Issue 12 (24th August 2015) - Karimi, Babak; Mansouri, Fariborz; Vali, Hojatollah
Abstract: Simple ion exchange of the chloride anion of an ionic‐liquid‐functionalized magnetic nanoparticle with [PdCl4 ] 2− provided a highly water‐dispersible and magnetically separable palladium catalyst that exhibited excellent activity toward transfer hydrogenation reactions in water as a solvent. The catalyst demonstrated outstanding performance in aqueous‐phase transfer hydrogenation of various nitroarenes in a highly chemo‐ and regioselective manner by using HCOONH4 as a low‐cost, green, and easily available hydrogen donor. Also, by using only 0.25 mol % of the catalyst and formic acid as both a hydrogen donor and formylating agent, the catalyst showed excellent activity in the one‐pot, direct synthesis of N ‐arylformamides from nitroarenes in water as a solvent. Notably, owing to the presence of a hydrophilic ionic liquid on the surface of silica‐coated iron oxide nanoparticles, the catalyst showed highly stable dispersion in water, as evidenced by the zeta potential and extremely low affinity to the organic phase. These features make this catalyst system suitable for an efficient double‐separation strategy (successive extraction/final magnetic separation). The recovered aqueous phase containing the catalyst can be simply and efficiently reused in eight runs without a decrease in activity and can be easily separated from the aqueous phase at the end of the process by applying an external magnetic field. Abstract : Going green : An ionic‐liquid‐functionalized magnetic nanoparticle containing palladium is a reusable, easily recoverable, highly selective, acid‐resistant, and switchable catalyst for transfer hydrogenation or the direct reductive N‐formylation of nitroarenes in water with readily available hydrogen donors (see scheme; TEG=triethylene glycol).